Darwinian adaptation of proteorhodopsin to different light intensities in the marine environment - Bielawski, Joseph P. (National Academy of Sciences, 2004)
Proteorhodopsin, a retinal-binding protein, represents a potentially significant source of light-driven energy production in the world's oceans. The distribution of photochemically divergent proteorhodopsins is stratified according to depth. Here, we present evidence that such photochemical diversity was tuned by Darwinian selection. By using a Bayesian method, we identified sites targeted by Darwinian selection and mapped them to three-dimensional models of proteorhodopsins. We suggest that spectral fine-tuning results from the combined effect of amino acids that directly interact with retinal and those that influence the confirmation of the retinal-binding pocket.